2019
DOI: 10.1016/j.chb.2018.12.042
|View full text |Cite
|
Sign up to set email alerts
|

MTurk participants have substantially lower evaluative subjective well-being than other survey participants

Abstract: Amazon's MTurk platform has become a popular site for obtaining relatively inexpensive and convenient adult samples for use in behavioral research. Concerns have been raised about selection issues, because MTurk workers chose to participate in the platform and select the tasks they perform (of many offered to them). Prior studies have documented demographic and psychological differences with national samples. In this paper we studied evaluative subjective well-being (the Cantril Ladder) in an MTurk sample, a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…A central concern that arises with engaging participants through online platforms, therefore, is whether the researchers (and the platform itself) compensate participants ethically (Bohannon, 2016; Lovett et al, 2018; Pittman & Sheehan, 2016). This is especially a concern in light of research that has shown that participants recruited through online platforms tend to have lower socio‐economic status, lower levels of well‐being (Stone, Walentynowicz, Schneider, Junghaenel, & Wen, 2019), and higher rates of clinical depression (Ophir, Sisso, Asterhan, Tikochinski, & Reichart, 2020) than the general population.…”
Section: Challenges Of Using Online Platforms For Data Collectionmentioning
confidence: 99%
“…A central concern that arises with engaging participants through online platforms, therefore, is whether the researchers (and the platform itself) compensate participants ethically (Bohannon, 2016; Lovett et al, 2018; Pittman & Sheehan, 2016). This is especially a concern in light of research that has shown that participants recruited through online platforms tend to have lower socio‐economic status, lower levels of well‐being (Stone, Walentynowicz, Schneider, Junghaenel, & Wen, 2019), and higher rates of clinical depression (Ophir, Sisso, Asterhan, Tikochinski, & Reichart, 2020) than the general population.…”
Section: Challenges Of Using Online Platforms For Data Collectionmentioning
confidence: 99%
“…A convenience sample of participants who were located in the United States, 21 years of age or older and who had patronized a bar was recruited using Amazon's Mechanical Turk (MTurk) platform. To increase the quality of responses, participants were also required to have an approval rate of previous requests of 95% or above [16]. In addition to that, the survey contained a combination of multiple-choice and openended questions.…”
Section: Methodsmentioning
confidence: 99%
“…Note that this sample of lay person reports was a convenience sample recruited through MTurk. Thus our findings are based on a specific subset of the population (younger, more educated, and more white; [ 73 ]) and may not generalize to other populations. Also, individual differences such as age might play a role in strategy effectiveness (e.g., older people might prefer paying by cash more than younger people).…”
Section: Study 3: Financial Self-control Strategies Reported In the Lay Populationmentioning
confidence: 99%